Effects of sandstone river aggregate on crumb rubber warm mix asphalt - Lillian @ Lilia Gungat; Mohd. Ishaq Selamat; Muhammad Saufi Sulaiman; Nurmin Bolong (UniSE Press, 2021)
The performance of asphalt pavement is influence by the quality of materials. However, Sabah does not have ample resources of good quality aggregate and have to rely on the sandstone aggregate. Hence, this study investigates the effects of sandstone river aggregate incorporating crumb rubber and warm mix asphalt additive. Laboratory study were carried out on specimen containing 0%, 10% and 20% crumb rubber as replacement of fine aggregate. Optimum binder content for each types of mixtures were determined in the mix design. Specimens prepared at optimum binder content were evaluated in terms of resilient modulus, dynamic creep and moisture susceptibility. Findings from the study indicated that inclusion of crumb rubber increased the optimum bitumen content. It was found that addition of 10% crumb rubber improved the resilient modulus dan resistance to permanent deformation compared with conventional hot mix asphalt. Specimen with 10% crumb rubber also showed the highest moisture susceptibility when added with hydrated lime. Hence, the most ideal crumb rubber content to be used in the road construction is 10%.